Wheat gene pool and its conservation in Nepal - Joshi, Bal K; Mudwari, Ashok; Bhatta, Madan R (Conservation Science, 2014)
Aim This paper explores diversity of wheat gene pool present in the Nepalese bread wheat cultivars and landraces, and discusses their conservation initiatives. Location Nepal. Material and Methods This study is carried out using an extensive literature survey on distribution of landraces and wild relatives of wheat in Nepal. Key findings The results showed that there were 35 improved wheat cultivars, 540 landraces and 10 wild relatives of wheat in Nepal. Mexico, India and Nepal were the countries of origin for 35 cultivars. A total of 89 ancestors of wheat originated from 22 countries were used to develop 35 cultivars. The highest number of ancestors was from India. Ancestors of both aestivum and durum species having winter, spring and intermediate growth habit indicated that these species were of wide gene pool. The genetic erosion in wheat gene pool is the main conservation challenge of landraces due to introduction of improved varieties. Conservation implications Genetic diversity of wheat is indispensible for sustainable wheat production. Therefore, on-farm and ex-situ conservations of cultivars, landraces and wild varieties of wheat and their use in breeding programs are necessary for maintaining existing genetic diversity. DOI: http://dx.doi.org/10.3126/cs.v1i1.9584 Conservation Science 2013 1(1), 39-46